Integrating ChatGPT into EFL writing instruction: Benefits and challenges - Baskara, FX Risang (Association for Scientific Computing Electrical and Engineering(ASCEE), 2023)
Teaching English as a Foreign Language (EFL) writing skills presents a unique set of challenges, from developing students' language proficiency to providing personalized feedback and support. In recent years, there has been growing interest in the potential of AI and NLP, such as ChatGPT, to support language education. This paper explores the potential benefits and challenges of using ChatGPT in EFL writing instruction. This paper is based on a review of relevant literature and highlights the potential of ChatGPT for EFL writing students. ChatGPT's ability to generate human-like text based on the input it receives makes it a potentially helpful tool for supporting students in their writing practice. Its natural language capabilities can engage and motivate learners. However, the potential challenges of using ChatGPT in language education are also discussed, such as the design, implementation and potential ethical concerns. This paper aims to provide a comprehensive overview of the potential benefits and challenges of integrating ChatGPT into EFL writing instruction. By exploring the potential of ChatGPT as a tool for language education, we aim to contribute to the ongoing debate on the role of technology and provide guidance for educators interested in using ChatGPT in their classrooms.